Los componentes material y finalista de la fiscalización administrativa: aproximaciones desde la doctrina, la normatividad y el control jurisdiccional efectuado en sede suprema - Cuba, Erick (2025)
Based on the doctrinal constructions and legal provisions related to administrative oversight, this paper analyzes the foundations of this activity, its current regulation, as well as its two defining components: the material execution and its purpose. Both components, material and final have been the subject of evaluation in the Supreme Court's cassations that have dealt with administrative oversight. Thus, this paper presents how these components have been safeguarded through jurisdictional control,having analyzed in the cases subject to litigation the rules that ensure its elements, taking as a reference the legal parameter of duties and obligations established in the current regulation contained in the Single Ordered Text of the Law of Sanctioning Administrative Procedure.